Fourth Five Year Plan 1969-74 A Draft Outline Government of Mysore - Planning Commission (Planning Commission, 1969)
The Draft Outline of the National and State Fourth Five Year Plan were prepared and released in the highly uncertain economic climate prevailing in the latter half of 1966. the Indo-Pakistan war had resulted in a sizeable diversion of resources from Development to defence and a suspension of foreign credit. The unprecedented severity of the drought of 1965-66 had forced large scale imports of pod grains, accelerated upward movement of prices and Compelled sanction of increased Dearness Allowances. then came the devaluation of the rupee.
Government of Mysore